Shedding Light on the Interfacial Structure of Low-Coverage Alkanethiol Lattices - Pensa, Evangelina Laura (2020)
A comprehensive description of the self-assembly process of alkanethiols on Au(111) is presented, focused on the initial formation of the lying down phases. Low-coverage monolayers are prepared by the disintegration of Au₁₄₄(RS)₆₀ nanoclusters on the reconstructed (22 × √3)-Au(111) surface. The method provides a limited number of thiols together with a large excess of gold adatoms. Scanning tunneling microscopy and density functional theory calculations were employed to study the transition between low to high thiolate coverage phases. The process involves different lattices and surface transformations, including thiyl radicals on the herringbone reconstruction, radicalinduced herringbone lifting, and the formation of energetically similar metastable phases formed by RS-Au-RS moieties. Results also show that the transition is slow, and different surface structures can coexist on the same sample. Along the process, the first source of Au adatoms to form the RS-Au-SR moieties is the lifting of the herringbone reconstruction because of the lower energetic cost to extract the extra Au atom. However, for hexanethiol (and shorter alkanethiols) at low coverage, additional Au adatoms must be taken from terraces leading to vacancy islands. This process can be entirely suppressed by growing the lying down phases in the presence of an excess of Au adatoms. Taken together, our results shed light on the elusive initial steps of thiol adsorption on clean reconstructed Au, showing that the RS-Au-SR staple motif is also present at the interface of low-coverage self-assembled monolayers.